2011
DOI: 10.1074/jbc.m110.203380
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Human Histone Methyltransferase ASH1L Catalytic Domain and Its Implications for the Regulatory Mechanism

Abstract: Absent, small, or homeotic disc1 (Ash1) is a trithorax group histone methyltransferase that is involved in gene activation. Although there are many known histone methyltransferases, their regulatory mechanisms are poorly understood. Here, we present the crystal structure of the human ASH1L catalytic domain, showing its substrate binding pocket blocked by a loop from the post-SET domain. In this configuration, the loop limits substrate access to the active site. Mutagenesis of the loop stimulates ASH1L histone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(137 citation statements)
references
References 24 publications
2
135
0
Order By: Relevance
“…This would be consistent with their proposed role in human cells, where the Trr and Trx homologs MLL1-2 and MLL3-4 are thought to methylate H3K4 at a limited number of non-overlapping gene targets (Wang et al 2009;Ansari and Mandal 2010;Eissenberg and Shilatifard 2010). We will not discuss the roles of Ash1 further, as recent findings suggest that the predominant function of Ash1 is the catalysis of H3K36, and not H3K4 methylation (Tanaka et al 2007;An et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This would be consistent with their proposed role in human cells, where the Trr and Trx homologs MLL1-2 and MLL3-4 are thought to methylate H3K4 at a limited number of non-overlapping gene targets (Wang et al 2009;Ansari and Mandal 2010;Eissenberg and Shilatifard 2010). We will not discuss the roles of Ash1 further, as recent findings suggest that the predominant function of Ash1 is the catalysis of H3K36, and not H3K4 methylation (Tanaka et al 2007;An et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In NSD1, the autoinhibitory loop is stabilized by a β-turn within the loop as well as hydrophobic contacts with SET-I [121]. In contrast, no β-turn exists in the ASH1L autoinhibitory loop, and there are longer range contacts to SET-I [120,127]. In the SETD2 autoinhibitory loop, there is also no β-turn to stabilize the loop, but the interaction of Arg1670 at the beginning of the loop with the substrate lysine-binding channel pulls the loop into contact with SET-I [122] ( Figure 3B).…”
Section: Structural Studies Of Nsd Ash1l and Setd2 Set Domains Demonstmentioning
confidence: 99%
“…For the H3K36-specific KMTases, structural studies of the catalytic SET domain have revealed valuable information to jumpstart inhibitor development. An important feature shared among the NSD, ASH1L and SETD2 SET domains is an autoinhibitory loop blocking access of histone substrate to the active site [120][121][122]. This loop must undergo a conformational change to accommodate substrate binding.…”
mentioning
confidence: 99%
“…However, unlike the much smaller protein ASH2L, ASH1L has not been identified so far as a member of the MLL protein complex. Recently, the ASH1L SET domain was reported to have intrinsic H3K36 dimethyltransferase activity using in vitro biochemical assays (37)(38)(39). Neither the physiological significance of Ash1l nor the idea of cooperativity with Mll1 and other TrxG members has been evaluated in vivo.…”
Section: Introductionmentioning
confidence: 99%